2013
DOI: 10.9775/kvfd.2012.8216
|View full text |Cite
|
Sign up to set email alerts
|

Erzincan Tulum Peynirinden İzole Edilen Staphylococcus aureus İzolatlarında Antibiyotik Direncinin ve Biyofilm Oluşturma Özelliğinin Fenotipik ve Genotipik Olarak Belirlenmesi

Abstract: SummaryIn this study, biofilm formation and antibiotic resistance of Staphylococcus aureus strains isolated from Erzincan tulum cheeses were phenotypically and genotypically investigated. Samples collected from 100 different Erzincan tulum cheese were inoculated into Baird-Parker agar to isolate S. aureus. Identification of S. aureus was performed with Gram staining, hemolysis or coagulase tests. Determination of the nuc, mecA, vanA, and vanB genes in isolates was performed by Polymerase Chain Reaction (PCR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
0
1
2
Order By: Relevance
“…Kanaan and Al-Shammary (2013) found MRSA phenotypically in 6 (40%) of the 15 soft white raw cheese with whey samples. This study's results are similar to those of Arefi et al (2014) and higher than other researchers' results (Huber et al, 2010;Yücel and Anıl, 2011;Özpınar, 2011;Mirzaei et al, 2011;Can and Çelik, 2012;Kanaan and Al-Shammary, 2013). These differences may be due to variations in cheese-production technology, the number of samples, and the fact that the milk used in production was not pasteurized.…”
Section: Discussionsupporting
confidence: 90%
“…Kanaan and Al-Shammary (2013) found MRSA phenotypically in 6 (40%) of the 15 soft white raw cheese with whey samples. This study's results are similar to those of Arefi et al (2014) and higher than other researchers' results (Huber et al, 2010;Yücel and Anıl, 2011;Özpınar, 2011;Mirzaei et al, 2011;Can and Çelik, 2012;Kanaan and Al-Shammary, 2013). These differences may be due to variations in cheese-production technology, the number of samples, and the fact that the milk used in production was not pasteurized.…”
Section: Discussionsupporting
confidence: 90%
“…Basanisi et al [24] reported this rate to be 41.1% in a study conducted on sheep and goat cheeses in Italy, which was higher than the rates found in this study, and as 61% in the study of Özpınar and Gümüşsoy [25] on 100 kinds of Erzincan Tulum cheese.…”
Section: Discussioncontrasting
confidence: 66%
“…Bu çalışmalardan birinde Erzincan'dan alınan tulum peynir örneklerinden izole edilen S. aureus izolatlarının %14.7'sinde oksasilin-metisilin dirençliliği tespit edilmiştir. Erzincan tulum peynirinin S. aureus ile kontaminasyon oranının yüksek olması ve izolatların antibiyotik dirençliliği göz önünde bulundurulduğunda halk sağlığı açısından risk oluşturabileceği ifade edilmiştir [49]. Bir başka çalışmada çiğ süt, peynir ve peynir altı suyundan oluşan toplam 81 örnekten izole edilen 40 adet S. aureus suşunun %15'inin oksasillin-metisilin direncine sahip olduğu saptanmıştır.…”
Section: Türkunclassified
“…İtalya'da yapılan bir çalışmada hayvansal kaynaklı gıdalardan elde edilen S. aureus izolatlarının içinde metisiline dirençli suşlar saptanmıştır [11]. Ulusal ve uluslararası literaturde Urfa peyniri kaynaklı S. aureus izolatlarında metisilin dirençliliğinin araştırıldığı bir çalışmaya rastlanmasa da geleneksel peynir kaynaklı izolatlarda metisilin direncinin yaygınlığına ilişkin yapılmış çeşitli çalışmalar bulunmaktadır [49,50]. Bu çalışmalardan birinde Erzincan'dan alınan tulum peynir örneklerinden izole edilen S. aureus izolatlarının %14.7'sinde oksasilin-metisilin dirençliliği tespit edilmiştir.…”
Section: Materyal Ve Metotunclassified